Illness representations, pain and physical function in patients with rheumatic disorders: between- and within-person associations. Issue 2 (1st February 2019) - Sindlinger, K.; Meng, K.; Dorn, M.; Faller, H.; Schuler, M.
Abstract: Objectives: Rehabilitation for patients with rheumatic diseases improves both illness representations (IR) and clinical outcomes such as pain and physical functioning (PF). However, it is unclear whether IR may affect and, in turn, are affected by pain and PF. In this study, we examined both between-person associations and within-person associations between IR and pain/PF over time on three measurement occasions. Furthermore, cross-lagged relationships were examined. Design and main outcome measures: This secondary analysis is based on data from N  = 186 patients with rheumatic diseases. Data on pain, PF and IR were assessed using self-report questionnaires at the beginning, the end and three months after a 3-week inpatient rehabilitation. Methods: To separate between- and within-person level, data were analysed using random-intercept cross-lagged panel models. Results: On both the between-person level ( r  = |0.21| − |0.44|) and the within-person level ( r  = |0.15| − |0.46|), pain and PF were related to cognitive and emotional IR. In addition, we found within-person bidirectional cross-lagged effects between emotional IR and PF. Conclusion: IR show complex relationships with pain and PF. Improving PF might improve subsequent illness-related emotional distress and vice versa.